Effectiveness of dexmedetomidine for emergence agitation in infants undergoing palatoplasty: a randomized controlled trial - Boku,Aiji (2016)
OBJECTIVES: In infants, there is a high incidence of emergence agitation (EA) after sevoflurane (Sev) anesthesia. This study aimed to test the hypothesis that dexmedetomidine (Dex) administration would reduce the incidence and severity of EA after Sev-based anesthesia in infants undergoing palatoplasty. METHODS: A prospective randomized clinical trial was conducted with 70 patients undergoing palatoplasty, aged 10-14 months. Infants were randomly allocated into two groups: Dex (n = 35) and saline (n = 35). In the Dex group, Dex (6 µg/kg/h) was administered approximately 10 min before the end of the surgery for 10 min, followed by 0.4 µg/kg/h until 5 min after extubation. In the saline group, an equivalent amount of saline was administered in a similar manner. After the surgery, patients were transferred to the postanesthetic care unit (PACU). The infant's behavior and pain were assessed with scoring system for EA (5-point rating scale) and pain scale (PS; 10-point rating scale), respectively. EA and PS were estimated at six time points (after extubation, leaving the operating room, 0, 30, 60, and 120 min after arrival in PACU). RESULTS: EA and PS scores were significantly lower in the Dex group than in the saline group from extubation to 120 min after arrival in PACU. CONCLUSIONS: Dex administration has the advantage of a reduced EA and PS without any adverse effects. Dex provided satisfactory recovery in infants undergoing palatoplasty.